The clinical significance of breast cancer stem cells (review of literature) - I. B. Schepotin; A. S. Zotov; R. V. Lyubota; N. F. Anikusko; I. I. Lyubota (ABV-press, 2014)
For a long time, in oncology dominated the stochastic theory of onset and progression of tumors, which postulated that any cell malignanttumor has tumorogenesis properties. However, currently there are more data indicating that the malignant tumors like normal tissues consistof several subpopulations of cells of various degree of differentiation, including stem. Thus, the alternative stochastic theory became a hierarchical theory of carcinogenesis. Like normal stem cells, cancer stem cells have natural resistance to radiation and systemic drug therapy, and may become the reason of occurrence of relapses and metastases. In this review analysed data regarding the clinical significance of breast cancer stem cells.